Perilaku Ibu Hamil dalam Pencegahan Malaria Berdasarkan Teori Health Belief Model - Wiwit Vitania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the behavioral factors of pregnant women in preventing malaria based on the theory of the health belief model in the Working Area of the Sentani Health Center, Jayapura Regency, Papua Province. The method used is qualitative research with a phenomenological approach. The results showed that perceptions about susceptibility, severity, and benefits could influence malaria prevention, and barriers and measures to prevent malaria become a mother's consideration for malaria prevention behavior. In conclusion, perceptions about susceptibility, severity, benefits, obstacles, and prevention of malaria influence malaria prevention behavior. Keywords: Health Belief Model, Malaria